Mir363-3p Treatment Attenuates Long-Term Cognitive Deficits Precipitated by an Ischemic Stroke in Middle-Aged Female Rats - Panta, Aditya; Montgomery, Karienn; Nicolas, Marissa; Mani, Kathiresh K.; Sampath, Dayalan; Sohrabji, Farida (Frontiers in Aging Neuroscience, 2020)
Cognitive impairment and memory loss are commonly seen after stroke and a third of patients will develop signs of dementia a year after stroke. Despite the large number of studies on the beneficial effects of neuroprotectants, few studies have examined the effects of these compounds/interventions on long term cognitive impairment. Our previous work showed that the microRNA mir363-3p reduced infarct volume and sensory motor impairment in the acute stage of stroke in middle-aged females but not males. Thus, the present study determined the impact of mir363-3p treatment on stroke-induced cognitive impairment in middle age females. Sprague Dawley female rats (12 months of age) were subjected to middle cerebral artery occlusion (MCAo) (or sham surgery) and injected (iv) with mir363-3p mimic (MCAo+mir363-3p) or scrambled oligos (MCAo+scrambled) 4h later. Sensory-motor performance was assessed in the acute phase (2-5d after stroke), while all other behaviors were tested 6 months after MCAo (18 months of age). Cognitive function was assessed by the novel object recognition test (declarative memory) and the Barnes maze (spatial memory). The MCAo+scrambled group showed reduced preference for a novel object after stroke, and poor learning in the spatial memory task. In contrast, mir363-3p treated animals were similar to either their baseline performance or to the sham group. Histological analysis showed significant deterioration of specific white matter tracts due to stroke, which was attenuated in mir363-3p treated animals. The present data builds on our previous finding to show that a neuroprotectant can abrogate the long-term effects of stroke.